Studi Rasionalisasi Jaringan Hidrologi Pulau Seram Provinsi Maluku - Mulya, Happy (MEDIA KOMUNIKASI TEKNIK SIPIL, 2014)
Information of water resources in the form of information on hydrological and hydro meteorological conditions, necessary to support the management of water resources in the basin (Law No.7/2004 SDA). This information is obtained from hydro-meteorological network that represents of these Basin. Rationalization aims to obtain efficient and effective hydrological network and can represent the hydrologic conditions of Seram Island Maluku Province both present and future. Therefore the selection of a method that only suggest the number, density or distribution of the post is not the final answer and directly elected, but the integration between the methods used by the method of Kagan, weight factor, and Stepwise with rules (standard, guidance, and manual) and considering spesific infrastructure needs existing and planned development in accordance with the pattern of river basin management. Proposed hydrology network for Seram Island is to maintain the existing number of hydrological station with the notes necessary of improvement efforts for hydrological management, such as to the amount of rainfall station are as many as 46 stations. Kagan analysis results for the basin with an area 4,873,382 km², has an error rate of 5% and 10% for the analysis, relatively small and good enough to be maintained.